Penyuluhan Hukum Pembuatan Akta oleh Notaris Berdasarkan Undang-Undang Nomor 2 Tahun 2014 Tentang Jabatan Notaris - Anthony Robert Phangestu Abady; Mella Ismelina Farma Rahayu (Journal on Education, 2023)
Notary is a public official who has the authority to make authentic deeds and has other authorities as referred to in Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning the Position of Notary. Notary as a capital market supporting profession to be able to make authentic deeds, and carry out activities in the capital market sector must first be registered with the Financial Services Authority (OJK), meet the requirements, and fill out an application for registration of a notary as a capital market supporting profession in the attachment to the Financial Services Authority regulations (OJK) Number 67/POJK.04/2017 Concerning Notaries Conducting Activities in the Capital Market. According to Article 1868 of the Civil Code, an authentic deed is a deed which, in the form determined by law, is made by or before public officials who have the power to do so at the place where the deed was made. The Authority of a Notary in Providing Legal Counseling for Making Deeds Based on the Notary Office Act (UUJN), a notary must educate the public or the parties who will draw up a deed before a notary regarding the rights and obligations of each party.